Articulations and tensions between General Didactics and Science Education: some analytical perspectives (Praxis Educativa, 2021)
The relationships between General Didactics (GD) and content-specific Didactics (CED), in this case, Science Education (SE) have proven to be fertile in theoretical-epistemological terms. But despite the progress in the consolidation of a fluid exchange, there are still controversial dimensions to continue deepening. For thisreason, we analyze, from own four perspectives, different dimensions and problems in order to identify and problematize articulations and emerging tensions in debates around GD and SE. The analysis perspectives that we construct are: 1- sociology of science; 2- historical-contextual; 3- investigation and / or intervention; and 4- curricular-institutional. Among other conclusions, we visualize a series of challenges to face, mainly related to the consolidation of a rich and fruitful interdisciplinary work that has a substantial impact on the improvement of teaching practices, from a socio-political project in which values of social justice prevail.
Keywords: Didactics; Science Education; disciplinary analysis; interdisciplinary dialogue